Online Hate Speech in the European Union: A Discourse-Analytic Perspective - Assimakopoulos, Stavros (SpringerBriefs in Linguistics, 2017)
hate speech research; discourse analysis of social media; corpus linguistics methods; C.O.N.T.A.C.T. project European Union; hate speech in reaction to news; racism in online comments forum; discourse analytic research